2010
DOI: 10.1095/biolreprod.110.086231
|View full text |Cite
|
Sign up to set email alerts
|

Activin A Balances Sertoli and Germ Cell Proliferation in the Fetal Mouse Testis

Abstract: Activin affects many aspects of cellular development, including those essential for reproductive fitness. This study examined the contribution of activin A to murine fetal testicular development, revealing contrasting outcomes of activin actions on Sertoli cells and gonocytes. Shortly after sex determination, from Embryonic Day 12.5 (E12.5) through to birth (0 dpp), the activin A subunit transcript (Inhba) level rises in testis but not ovary, followed closely by the Inha transcript (encoding the inhibitory inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 55 publications
7
92
1
1
Order By: Relevance
“…However, in the same study, RA was reported to slightly increase PND3 gonocyte numbers and have no effect on apoptosis. Moreover, activin A and androgen were reported to be negative regulators of fetal gonocyte proliferation, whereas we did not find any effect of testosterone on PND3 gonocyte proliferation in vitro (Merlet et al 2007, Thuillier et al 2010, Mendis et al 2011.…”
Section: Introductioncontrasting
confidence: 86%
“…However, in the same study, RA was reported to slightly increase PND3 gonocyte numbers and have no effect on apoptosis. Moreover, activin A and androgen were reported to be negative regulators of fetal gonocyte proliferation, whereas we did not find any effect of testosterone on PND3 gonocyte proliferation in vitro (Merlet et al 2007, Thuillier et al 2010, Mendis et al 2011.…”
Section: Introductioncontrasting
confidence: 86%
“…In contrast to these findings however, another study concluded that disruption of Activin/Nodal signaling affected fetal germ cell meiosis (although pluripotency was not investigated) (Souquet et al 2012). In that study, Activin/Nodal inhibitors disrupted Nodal signaling in germ cells but also Activin signaling in somatic cells, so it is possible that the observed meiosis is the result of inadvertent disruption of the gonadal environment: Activin is normally required for the induction of germ cell mitotic arrest and differentiation (Mendis et al 2010). Complete Nodal deletion in germ cells may be required to clarify whether the main role of Nodal signaling is to maintain pluripotency or to prevent meiosis.…”
Section: Model Of Nodal Signaling Nodal a Member Of The Tgfb Famimentioning
confidence: 82%
“…Multiple Tgfβ superfamily members have also been associated with male germ cell differentiation, including Tgfβ2 (Miles et al, 2013;Moreno et al, 2010) and activin β 5 (InhbaMouse Genome Informatics) (Mendis et al, 2011). These factors repress germ cell proliferation, and participate in the entry into quiescence (Moreno et al, 2010) and probably also in its maintenance (Mendis et al, 2011;Moreno et al, 2010).…”
Section: Introductionmentioning
confidence: 99%